HUBUNGAN PENGETAHUAN TENTANG OSTEOPOROSIS DENGAN PENCEGAHANOSTEOPOROSISPADA LANJUT USIA DI DUSUN PUHREJO DESA TULUNGREJO KECAMATAN PARE KABUPATEN KEDIRI - Mubaidah, Siti; Hareni, Risti Dwi (Akademi Keperawatan Pamenang, 2010)
Osteoporosis is a chronic disease and attact especially for elderly. Because of the impact of itsdisease, people which affect by this problem may suffer for whole of his or herl life. To avoid from thisdisease, people should perform health life style to prevent or to cure this problem getting worse. Theobjective of this research was to infestigate are there any relationship between the knowledge of the elderlyto their behavior in prevent the osteoporosis at Puhrejo hamlet, Tulungrejo village Pare Subdistrict Kediri.The research design was analytic by crossectional approach. The population of the study was allelderly in Puhrejo Tulungrejo village Pare Subdistrict Kediri Region as many as 39 elderly.The sampleswastaken by simple random sampling and the data collection held by questioner. Then data analyzedwithdescriptive statistic and followed by Contingency coefficient test as inferential statistics.Result of the study was : the level of knowledgeof respondents on osteoporosis are 27 respondent(77,1%) was good, 6 respondent (17,1%) were fair and only 3 persons (5,7%) were poor While thepreventive behavior of the respondents were: 25 (71,4%) perform preventive behavior and the others did notperform preventive behavior. According to Coefficient contingency test to figure the relationship betweenknowledge and osteoporosis prevention-behavior of elderly, the significance value was (2-tailed)0,006<0,005 (Î±), meant that there was a significant relationship between both variables.Following the result of the study, itâs important to increase the knowledge of elderly to prevent theincidence of osteoporosis by performing osteoporosis preventive behavior.